Association Between Sex Hormones and Visual Field Progression in Women With Primary Open Angle Glaucoma: A Cross-Sectional and Prospective Cohort Study - Qiu, Yichao; Yu, Jian; Tang, Li; Ren, Jun; Shao, Mingxi; Li, Shengjie; Song, Yunxiao; Cao, Wenjun; Sun, Xinghuai (Frontiers in Aging Neuroscience, 2021)
Purpose: We evaluated the level of sex hormones in female primary open angle glaucoma (POAG) patients to determine whether they are associated with the onset and/or progression of POAG. Methods: The cross-sectional study enrolled 63 women with POAG and 56 healthy women as normal control subjects. Furthermore, 57 women with POAG were included and followed-up for at least two years in the cohort study. All subjects were evaluated for serum concentration of sex hormones [prolactin (PRL), luteinizing hormone (LH), testosterone (TESTO), follicle-stimulating hormone (FSH), progesterone (PROG), and estrogen (E2)] and underwent visual field (VF) examination. In the cross-sectional study, Spearman analysis, linear regression analysis, and logistic regression analysis were performed to assess risk factors for POAG in females. In the cohort study, Cox regression analyses and Kaplan-Meier survival analysis were performed to identify factors associated with VF progression in women with POAG. Results: In the cross-sectional study, the level of E2 was significantly lower in the POAG group than in the normal group (P<0.05). Multiple logistic regression showed that the decreased level of E2 was a risk factor of POAG (OR=0.27, 95% CI=0.09 – 0.78, P<0.05), especially in premenopausal subjects. In the cohort study, there were 29 non-progression subjects and 28 progression subjects. Patients in the progression group had significantly lower levels of E2 than those in the no progression group (P<0.01). The decreased level of E2 at baseline was associated with POAG progression (HR=0.08, 95% CI=0.02 – 0.46, P<0.05), especially in premenopausal subjects. POAG patients with lower baseline E2 levels had significantly lower VF non-progression rates than patients with higher E2 levels (log-rank test P<0.001), especially premenopausal subjects (log-rank test P<0.05). Additionally, logistic regression analyses, Cox regression analyses, and Kaplan-Meier survival analysis showed that PROG, LH, FSH, and TESTO were risk factors of POAG and/or significantly associated with POAG progression. Conclusions: A decreased E2 level is a POAG risk factor and is associated with VF progression in women with POAG, especially in premenopausal subjects. Additionally, other sex hormones (PROG, LH, FSH, and TESTO) might also play a role in POAG pathogenesis.